health HUBUNGAN SUMBER INFORMASI DENGAN PENGETAHUAN REMAJA PUTRI TENTANG PENANGANAN PREMENSTRUASI SINDROM DI SMPN 3 KARANG INTAN KAB.BANJAR: HUBUNGAN SUMBER INFORMASI DENGAN PENGETAHUAN REMAJA PUTRI TENTANG PENANGANAN PREMENSTRUASI SINDROM DI SMPN 3 KARANG INTAN KAB.BANJAR - Qomah, Isti; Aulia, Nor Aina (Journal of Health Management, Administration and Public Health Policies, 2024)
Knowledge of Premenstrual Syndrome (PMS) is very important for women because almost all women who menstruate experience symptoms of Premenstrual Syndrome and teenagers who experience menstrual symptoms can interfere with daily and emotional activities as much as 74%. The lack of information and the lack of role of parents in the management of Premenstrual Syndrome is often one of the problems that makes them less correct in making decisions. Each person's behavior in dealing with premenstrual syndrome is different depending on the human response. Human behavior is an activity that arises due to stimulus and response and can be experienced directly or indirectly. This research design uses an analytical survey method with a cross sectional approach. Independent variables include sources of information and the dependent variable is knowledge of young women. The majority of respondents never received information as many as 22 respondents (48.8%) and some respondents had less knowledge as many as 15 respondents (20.9%), based on the results of the Chi Square test it was found that there was a relationship between the source of information and the knowledge of young women about treatment. premenstrual syndrome (PMS) with p value = 0.036. There is a relationship between sources of information and knowledge of young women about handling premenstrual syndrome. Keywords: Sources of Information, Knowledge, Management of premenstrual syndrome